The Effect of Profitability, Capital Structure and Dividend Policy on Company Value - Wibowo, Vanisaharani Septania; Suwardi , Suwardi (Economics and Business International Conference Proceeding, 2024)
This study aims to find out the Influence of Profitability, Capital Structure and Dividend Policy on Company Value in Conventional Banking Listed on the Indonesia Stock Exchange for the 2019-2022 Period. Data is taken from financial statements from 2019-2022. The selection of samples in this study uses the purpose sampling method. The number of companies sampled based on the criteria set was 16 companies. Hypothesis testing uses normality tests, t- tests, F tests and determination tests using SPSS (Statistical Package for the Social Sciences) as a tool in calculations. The results of the study show that (1) Profitability has a significant positive effect on Company Value (2) Capital Structure has a significant negative effect on Company Value. (3) The Dividend Policy has a positive effect on the company’s value. For the next research, it is recommended to explore other factors that may affect the Company’s Value.